The fifth risk undoing democracy - Lewis, Michael (New York W.W. Norton & Company, 2018)
The morning after Trump was elected president, the people who ran the US Department of Energy - an agency that deals with some of the most powerful risks facing humanity - waited to welcome the incoming administration's transition team. Nobody appeared. Across the US government, the same thing happened: nothing.
Keywords: United States--Politics and government--2017-